Optimization of School Health Unit at Islamic Boarding School - Wardiansyah; Indri Seta Septadina (Arkus, 2020)
School Health Unit (SHU), is an effort made by schools to help students and school residents who are sick in the school area. SHU is usually done in the health room of a school. In another sense, SHU is an effort to foster and develop healthy habits and behavior in school age students which is carried out comprehensively (comprehensively) and integrated (integrative). To optimize the SHU program, the participation of students as subjects and not just objects needs to be increased.